Well-ordered self-assembled monolayer surfaces can be used to enhance the growth of protein crystals - Pham T. (2014)
A series of hydrophobic self-assembled monolayers (SAMs) was generated by the adsorption of undecanethiol, dodecanethiol, and octadecanethiol onto transparent gold-coated glass microscope slides. Protein crystallization trials using droplets deposited on the surfaces of the optically transparent SAMs were compared to those for which the droplets were deposited on the surfaces of conventional silanized glass microscope slides. For the five distinct proteins examined in the crystallization trials (i.e., lysozyme, α-lactalbumin, hemoglobin, thaumatin, and catalase), the SAMs generally afforded, (1) a faster rate of crystallization, (2) a larger crystal size; and (3) a broader range of crystallization conditions than that afforded by silanized glass. The greatest enhancements were observed with the highly ordered SAMs derived from octadecanethiol, which are evaluated here for the first time. © 2004 Elsevier B.V. All rights reserved.